Mineração e licenciamento ambiental: aspectos jurídicos e sua efetividade - Lopes, Márcio Mauro Dias (2016)
This research aims at contextualizing and analyzing the legal aspects of mining and environmental permitting in order to develop a methodology to assist in the management of mining activities from the preliminary stages to the closure of the mine, focusing on mitigation and treatment of significant environmental impacts and hazards and risks related to the health of mining workers. As a research method in office, analysis of the regulatory system, ore exploitation regime in the country, and survey of directly applicable law were used. To compose the variables of the study data obtained in active field of a mining company we used. This research is justified for understanding that in practice elements are missing so that conflicts resulting from the exercise of mining activities and their externalities are resolved through a transparent management. Finally, as a result it was possible to develop a methodology of practical application to assist mining activities in the analysis of significant environmental aspects and impacts, as well as hazards and risks related to occupational health and safety of mining workers, underpinned by management programs whose effectiveness is measured based on performance indicators